Pengaruh ketersediaan Prasarana Dan Sarana Terhadap Nilai Lahan Pemukiman di Makassar - Nurdin Kasim, Noviar; Achmad Gani, Pratiwi Juniar (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2016)
The development of the population that is increasingly congested, so the need for housing will also increase. It looks from the development efforts to increasing the number of housing development, both held by the government (Perum Perumnas) and by the private sector. According to UU Tata Ruang where it is stated that any housing development should be supported by the availability of infrastructure and facilities. But these provisions required and sometimes not at all met, there are still a lot of housing that do not have infrastructure and facilities in accordance with the provisions required. This research aims to determine whether the availability of infrastructure and facilities for a significant effect on the value of residential land in Makassar and to measure the level of significance of the effect of the availability of infrastructure and facilities to the value of residential land in Makassar. The methods of this research used is quantitative research explanatory which is a type of research that describes the influence of the independent variable on the dependent variable to test the hypothesis. The resulting findings that infrastructure and facilities contributing to influence on the value of land for housing at 65% and 46.5%. With the availability of infrastructure and housing facilities. then the value of land owned by a housing becomes higher. Members of the independent variable for infrastructure where being the most dominant to gives an effect on the value of land is the road infrastructure and a member of the independent variables for facilities where being the most dominant to gives an effect on the value of land is an education facilities